Growth of semi-polar (11-22) GaN epitaxial layer on M-plane sapphire via MOCVD / Mohd Afiq Anuar - Mohd Afiq , Anuar (2020)
In the past few years, semi-polar (11-22) GaN has attracted much intention in the field of optoelectronics including light-emitting diodes (LEDs), laser diodes (LDs) and photodetectors. Commercially, GaN-based optoelectronic devices are grown along c-plane direction. However, c-oriented GaN-based optoelectronics suffer from piezoelectric polarization, which hinders the device performances. Conversely, semi-polar (11-22) GaN exhibits almost zero piezoelectric polarization effect. Furthermore, as the GaN wurtzite lattice is inclined approximately 58° respective to c-plane, it provides more sites for doping incorporation such as indium, silicon, aluminium, etc. Therefore, the semi-polar (11-22) GaN is presumed to be one of a promising candidate for efficient device applications. However, semi-polar GaN suffers from numerous crystal defects during the epitaxial process leading to poor crystal quality as well as surface properties. For decades, various approaches have been implemented to achieve an enhanced morphological and crystal quality of semi-polar (11-22) GaN. These approaches include the epitaxial lateral overgrowth (ELOG), surface selective growth on patterned substrates (SSG), and overgrowth on nano-rod array templates. However, such approaches require additional complex ex-situ processes with the use of dielectric materials. In addition, studies have also shown enhanced crystal qualities upon the utilization of in-situ techniques such as AlN/GaN multilayer and SiN interlayer. Nonetheless, such techniques require additional metal sources. In this study, enhanced surface morphological and crystal properties of semi-polar (11-22) gallium nitride (GaN) was successfully achieved via implementing an In-Situ Multiple Ammonia Treatment (I-SMAT) method. Utilization of an optimized flow of ammonia (2.3 SLM), surface striations of semi-polar (11-22) GaN was reduced yielding RMS roughness of 3.07 nm. Low scan sizes of the surface reveal an evolution of the atomic-sized terraces to a rather uniformly arranged distribution resulting in narrowing/shallowing of the interfacial valleys. X-ray rocking curve (XRC) analysis implies that I-SMAT would facilitate dislocation reduction through a selective-area etching process consequently enhancing the crystal quality. Conversely, excessive ammonia flux during the I-SMAT would degrade the structural and morphological properties of the semi-polar epilayer whereby the alternating thin GaN epilayer would undergo the selective-area etching to the extreme.